Evaluating the Effectiveness of Learning Transfer - Proposed Model for the Public Administration and Administration Development Institutes in the GCC (Gulf Cooperation Council) Countries. - Sridhar, Mani (2013)
Research from all over the world shows that trainees consistently rate training content as not being strongly related to what they need on their jobs. In addition, they typically say that the content is not taught in a way what that they know how to apply it on their jobs(Translogix Research, 2009). The aim of this paper is to examine the learning transfer effectiveness commencing with Learning Process (from knowledge to performance capability) to Work Process (from performance capability to sustained performance) for the training and development initiatives of the Public Administration and Administration Development Institutes in the GCC countries and propose a refined model of training transfer.